Formulation and Effectiveness Test of Eschericia coli Bacteria Organic Liquid Soap Preparations Aloe Vera Leaf (Aloe Vera Linn) - Nafisah Isnawati (UrbanGreen, 2020)
Research on organic liquid soap formulations and the effectiveness test of Echericia coli bacteria from Aloe vera (Aloe vera linn) have been conducted. This research aims to formulate and test the effectiveness of liquid soap preparations using natural ingredients. The formulation is made by aloe vera leaves, sodium chloride, suji leaf coloring, and the lime scent with concentrations of 10%, 25%, and 50%. The results of the research organoleptic test process were the results of soap preparations with liquid texture, the lime scent and the typical green color of suji leaves. The pH of the observations was 6 for various concentrations. High liquid soap foam with 10% concentration obtained an average of 89.27 mm, a concentration of 25%, 69.46 mm, and a concentration of 50% with an average of 52.05 mm. the result of liquid test specific soap obtained from 10% concentration is 1.037g / ml, 25% concentration is 1.048 g / ml and 50% concentration is 1.059 g / ml. the resultsof research obstacles zone on Echericia coli bacteria obtained an average of 16.7 mm for a concentration of 10%, 18.7 mm for a concentration of 25%, and a obstacles zone of 22.7 mm for a concentration of 50% and for irritation test 100% found no irritation.